Produkcyjne i ekonomiczne aspekty uprawy dwóch różnych typów użytkowych roślin energetycznych na przykładzie wierzby i rzepaku - Sadowski, Arkadiusz; Jankowiak, Janusz (Production and Economic Aspects of Two Types of Energy Crops Cultivation on the Example of Willow and Rape, 2009)
The aim of the paper is to present some economic and production aspects of energy crops cultivation on the example of energy willow for biomass and rape for biodiesel. The development of renewable energy depends on many political and market factors. The results of the discounted cash flow indicate that financial surplus is larger in willow cultivation. The financial aspect is important, but environmental and market aspects are also crucial. Soil demands are different for these two crops. Rape needs good soil. Willow can be cultivated on barren soil and it can be an important factor of marginal land arrangement. Marketing aspects are also significant. Willow belongs to permanent crops, so the perspective of market stabilization is uncertain, especially in the context of investigation of new energy sources. Rape on the contrary makes possible more flexible reaction for the permanent changes of external conditions on the biofuel market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 287-295